Declining memberships, changing members? European political party members in a new era - Scarrow, Susan E.; Gezgor, Burcu (Party politics)
In recent years, membership in established political parties has been shrinking, but at the same time members of some parties have received increased powers to help select candidates, leaders and party policies. These twin trends make it important to re-examine who is joining today’s smaller parties. As parties shrink, do they attract a changed mixture of members, possibly with different political priorities? Using data from two sets of European surveys, our study investigates this question to study longitudinal change in party membership. The data show a growing gap between the age of party members and the general population. In most other respects, however, party members seem to be becoming more, not less, like their fellow citizens. This suggests that today’s smaller but more powerful memberships still have the potential to help link their parties to a wider electoral base.